Sex Influences the Genetic Structure of Greenland Halibut in the North Atlantic - Daniel Estévez‐Barcia; Denis Roy; Mikko Vihtakari; Davíð Gíslason; Martin Lindegren; Asbjørn Christensen; Laura Wheeland; Margaret Treble; Julio Úbeda; Adriana Nogueira; Kevin Hedges; Áki Jarl Láruson; et al. (Ecology and Evolution)
ABSTRACT Greenland halibut (Reinhardtius hippoglossoides) is a commercially important species in the North Atlantic whose spatial population structure has not yet been fully determined across its entire range. We genotyped individuals from across the North Atlantic using a subset of informative single nucleotide polymorphic (SNP) markers to assess their usability as a SNP panel. We assessed whether these purportedly structured SNPs had any association with sex. We found several of these loci to be in sex‐determining chromosomes and that their inclusion generated genetic structure mainly in males. The population structure without the sex‐associated SNPs was weak and followed an isolation‐by‐distance pattern, likely with a large regional population on each side of the North Atlantic. We discuss how different sex ratios in the samples and/or an evolving sex‐determination system in this species likely caused the inclusion of sex‐associated loci in the panel. We found suggestive evidence of polymorphisms at sex‐determining chromosomes differentiating males on east and west locations, indicating evolution of the sex‐determination system. These results highlight the importance of documenting sex‐based differences in genetic studies and call for a better understanding of genomic architecture to understand sex‐determination systems across the whole distribution of sexually dimorphic species.